A Comprehensive Assessment of Co-occurring Birth Defects among Infants with Non-Syndromic Anophthalmia or Microphthalmia. (3rd September 2021) - Schraw, Jeremy M.; Benjamin, Renata H.; Scott, Daryl A.; Brooks, Brian P.; Hufnagel, Robert B.; McLean, Scott D.; Northrup, Hope; Langlois, Peter H.; Canfield, Mark A.; Scheuerle, Angela E.; Schaaf, Christian P.; Ray, Joseph W.; et al.
ABSTRACT: Purpose: Infants with anophthalmia or microphthalmia frequently have co-occurring birth defects. Nonetheless, there have been few investigations of birth defect patterns among these children. Such studies may identify novel multiple malformation syndromes, which could inform future research into the developmental processes that lead to anophthalmia/microphthalmia and assist physicians in determining whether further testing is appropriate. Methods: This study includes cases with anophthalmia/microphthalmia identified by the Texas Birth Defects Registry from 1999 to 2014 without clinical or chromosomal diagnoses of recognized syndromes. We calculated adjusted observed-to-expected ratios for two – through five-way birth defect combinations involving anophthalmia/microphthalmia to estimate whether these combinations co-occur more often than would be expected if they were independent. We report combinations observed in ≥5 cases. Results: We identified 653 eligible cases with anophthalmia/microphthalmia (514 [79%] with co-occurring birth defects), and 111 birth defect combinations, of which 44 were two-way combinations, 61 were three-way combinations, six were four-way combinations and none were five-way combinations. Combinations with the largest observed-to-expected ratios were those involving central nervous system (CNS) defects, head/neck defects, and orofacial clefts. We also observed multiple combinations involving cardiovascular and musculoskeletal defects. Conclusion: Consistent with previous reports, we observed that a large proportion of children diagnosed with anophthalmia/microphthalmia have co-occurring birth defects. While some of these defects may be part of a sequence involving anophthalmia/microphthalmia (e.g., CNS defects), other combinations could point to as yet undescribed susceptibility patterns (e.g., musculoskeletal defects). Data from population-based birth defect registries may be useful for accelerating the discovery of previously uncharacterized malformation syndromes.